Sistem Pakar Mendiagnosa Penyakit Appendisitis Menggunakan Metode Certainty Factor - Feryra, Stivano; Suranti , Dewi; Yupianti (Jurnal Komputer, 2023)
Health is an important asset in carrying out activities so it needs to be maintained and considered properly, therefore it is important to equip yourself with knowledge and maintain a healthy lifestyle in order to avoid various diseases. One of the diseases that attack humans and is often found in hospitals is appendicitis. The lack of knowledge and socialization to the community about this disease Appendicitis (Inflammation of the Appendix), resulting in the community considering this disease as trivial or ordinary, in fact according to the information of doctors this disease which if not treated properly will cause death. Therefore, to help the community and medical personnel in providing knowledge, consultation and socialization about the disease Appendicitis (Inflammation of the Appendix) is to design and build an expert system application by applying the Certainty Factor method. The Certainty Factor method has the advantage of being able to measure something whether it is certain or uncertain, for example in diagnosing a disease.The final result of this research is an expert system to diagnose Appendicitis (Inflammation of the Appendix) along with the confidence value of the diagnosed disease, which shows the system's level of confidence in the disease.